A chronology of medieval British history 1066-1307 - Venning, Timothy, author.
1 online resource
Keywords: "A Chronology of Medieval British History 1066-1307 covers events in British history, starting with the arrival of the new Norman ruling dynasty which 'connected' British politics, culture, religion, and society more closely to mainland Europe, and ending with Edward I's death and Robert Bruce's revolt in 1307"--